Mindful Learning: Principles and Prospect of Use in Higher Education - A.K. Bordunos; M.P. Miletich; N.V. Volkova (Moscow State University of Psychology and Education, 2024)
The article provides an overview of the principles of mindful learning in the context of higher education. Mindful learning is an approach in which students and teachers tune their attention to increasing value and awareness of what is happening in the surrounding context, to their experience and reflection about it. The relevance of the research is related to the interest in the effects associated with mindful learning: positive impact on psychological well-being, development of socio-emotional skills, as well as increasing intrinsic motivation, improving attentiveness and concentration of students. The article reviews research indicating the effectiveness of this approach for both learning outcomes and the psychological well-being of students and teachers in the educational process. The theoretical contribution of this research lies in highlighting the research agenda in the field of mindful learning: defining concepts of mindful learning and mindful teaching, identifying the main principles of mindful learning. These results provide a basis for further research of mindful learning in higher education. The practical contribution of the research lies in presenting a methodological basis for introducing mindful learning into university disciplines. The research may be of interest not only to teachers and methodologists but also to students and their parents due to the increased interest in the effects of mindful learning.